Dampak Media Gadget terhadap Perkembangan Sosial Emosional Anak Usia Dini - Semiana Hasibuan; Saima Sakilah Dalimunthe (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The research aims to find out how the role and impact of gadget media on early childhood emotional social development and how to solve the use of gadgets media on the emotional development of early children. As for the type of research used, qualitative research with qualitatively descriptive approaches, data collection techniques used in the form of observations, interviews and documentation, while data analysis techniques used are data display, data verification and data conclusion. Research shows that the role and impact of gadget media on early childhood emotional social development plays a huge role in children's needs in learning by following technological developments in fulfilling their school duties, but not apart from the positive and negative impact that accompanies them. This research is expected to contribute to the social development of children, parents and educators.